2020
DOI: 10.1097/iop.0000000000001880
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Automated Computed Tomography Volumetric Analysis Metrics With Motility Disturbances in Thyroid Eye Disease

Abstract: Purpose: The authors sought to examine relationships between CT metrics derived via an automated method and clinical parameters of extraocular muscle changes in thyroid eye disease (TED). Methods: CT images of 204 orbits in the setting of TED were analyzed with an automated segmentation tool developed at the institution. Labels were applied to orbital structures of interest on the study images, which were then registered against a previously established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…We thank Li et al for their comments on our thyroid eye disease research. 1 We agree with the authors that additional validation of automated segmentation in thyroid eye disease is needed. Validation of any measurement tool is important, and we have done it.…”
Section: To the Editorsupporting
confidence: 82%
See 1 more Smart Citation
“…We thank Li et al for their comments on our thyroid eye disease research. 1 We agree with the authors that additional validation of automated segmentation in thyroid eye disease is needed. Validation of any measurement tool is important, and we have done it.…”
Section: To the Editorsupporting
confidence: 82%
“…We demonstrate that Kalman filters provide a simple, yet fast and efficient solution to improving muscle segmentation in thyroid eye disease. 1,6,10…”
Section: To the Editormentioning
confidence: 99%
“…We read with great interest the article “Correlation of Automated Computed Tomography Volumetric Analysis Metrics With Motility Disturbances in Thyroid Eye Disease” wherein Law et al 1 employ an automated segmentation method developed using normal orbital CT images to characterize relationships between CT metrics and clinical findings in patients with thyroid eye disease. Using this automated method, the authors concluded that ocular motility deficits were correlated with superior, inferior, and lateral recti average diameter, maximum diameter, and volume, and medial rectus volume.…”
Section: To the Editormentioning
confidence: 99%
“…Using this automated method, the authors concluded that ocular motility deficits were correlated with superior, inferior, and lateral recti average diameter, maximum diameter, and volume, and medial rectus volume. 1…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation